Domestic Violence, Drug & Alcohol Abuse Including Types of Anger in Indian Culture in India and Abroad: Exploring the relationship between substance abuse, domestic violence, and anger in Indian culture (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Alcohol’s role in men’s violence against women is a controversial issue. Many articles have been written that we read in the newspapers that teens are being held for consuming drugs & alcohol and most of them are usually aged between 17-20. But the main question arises that why the Indian society is experiencing such a dilemma where more of the teenagers and youths are involved in unethical, non-societal and unproductive activities like substance or drug abuse. This research paper studies about domestic violence, drug / alcohol abuse and types of anger in Indian culture in India and abroad.